Onset and Progression of Pathologic Atrophy in Huntington Disease: A Longitudinal MR Imaging Study - Hobbs, N.Z.; Barnes, J.; Frost, C.; Henley, S.M.D.; Wild, E.J.; Macdonald, K.; Barker, R.A.; Scahill, R.I.; Fox, N.C.; Tabrizi, S.J. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Longitudinal MR imaging measures provide an opportunity to track progression in HD before the emergence of clinical symptoms. This may prove useful in assessing disease-modifying treatments. We investigated how caudate and global volumes change as HD progresses from premanifest to early disease. MATERIALS AND METHODS: Forty HD gene-positive individuals and 19 controls underwent serial volumetric MR imaging (baseline, 12 and 27 months; 2 or 3 scans per person). At baseline, 3 patients with HD were premanifest but developed overt motor features during the study, and 37 had early HD. All had dates of motor onset recorded. Caudates, lateral ventricles, and TIVs were measured using semiautomated procedures. Linear mixed models were used to investigate differences between HD and controls in relation to motor onset, controlling for TIV, sex, and age. RESULTS: Extrapolating backwards in time, we found that differences in caudate and ventricular volumes between patients with HD and controls were evident 14 and 5 years, respectively, before motor onset (P < .05). At onset, caudate volume was 2.58 mL smaller than that in controls (P < .0001); ventricular volume was 9.27 mL larger (P < .0001). HD caudate atrophy rates were linear, showed low variability between subjects, and were approximately 10-fold higher than those in controls (P < .001). HD ventricular enlargement rates were variable between subjects, were approximately 4-fold higher than those in controls at onset (P < .001), and accelerated with disease duration (P = .02). CONCLUSIONS: We provide evidence of acceleration of global atrophy in HD with disproportionate caudate involvement. Both caudate and global measures may be of use as early markers of HD pathology. CIconfidence intervalDurdisease duration (time since motor onset)HDHuntington diseaseICCintraclass correlation coefficientMBImean brain intensityNHNNNational Hospital for Neurology and NeurosurgeryNIHRNational Institute for Health ResearchTIVtotal intracranial volumeUCLUniversity College LondonUHDRSUnified Huntington's Disease Rating Scale